REGULATING COGNITIVE LOAD: PRIOR KNOWLEDGE ACTIVATION IN LEARNING ECOSYSTEM - Dzihni Andiasari (Jurnal Pengajaran MIPA, 2022)
The ecosystem is a multidiscipline and complex subject which interrelated with other biological concepts, making it challenging to understand and may lead to cognitive overload. This paper analyzed the effects of prior knowledge activation using video on students' cognitive load when learning about the ecosystem. Data were obtained from prior knowledge tests, a task complexity worksheet, a subjective rating scale, and reasoning ability tests as learning achievement. The effect of prior knowledge activation using video on intrinsic cognitive load (ICL) and extraneous cognitive load (ECL) was evaluated and discussed.